Level of risk for alcohol consumption among the drivers of an urban public transportation company in Medellín - Carlos F. Molina C; Ana M. Suarez B; Catalina M. Arango A (Universidad de Antioquia, 2011)
Objective: to study the level of risk for alcohol consumption among drivers from a public transportation company. Methodology: a cross-sectional observational study with a sample of 145 drivers from a transportation company in Medellin, Colombia. A self-survey was used that included socio-demographic data, work organization data, and the audittest to measure the level of risk for alcohol consumption. Results: the socio-demographic and work organization profiles, together with the risk level values are consistent with the findings of previous national and international studies. The audit test results showed that 12.5% of the subjects had a score greater than or equal to 8. This is a global indicator of risky and harmful consumption. Furthermore, the score of 17% of the subjects suggested probable dependence. Conclusions: this study's findings suggest that further research is required in order to establish the grounds for designing a coordinated proposal integrating the actions of each of the Social Security System's actors. Such proposal should be based on the policy for decreasing consumption of psychoactive substances in the working population